Psychology in social context : issues and debates - Tyson, Philip John.; Jones, Dai, 1943-; Elcock, Jonathan (Chichester, UK. : BPS Blackwell, 2011)
'Psychology in Social Context: Issues and Debates provides a critical perspective on debates and controversies that have divided opinion within psychology both past and present. Explores the history of psychology through examples of classic and contemporary debates that have split the discipline and sparked change, including race and IQ, psychology and gender, ethical issues in psychology, parapsychology and the nature-nurture debate Represents a unique approach to studying the nature of psychology by combining historical controversies with contemporary debates within the discipline Sets out a clear view of psychology as a reflexive human science, embedded in and shaped by particular socio-historical contexts Written in an accessible style using a range of pedagogical features - such as set learning outcomes, self-test questions, and further reading suggestions at the end of each chapter'--
'In recent years there has been increased recognition of the weaknesses within orthodox views of psychology, and this has led to a surge in critical approaches to the discipline. Reflecting this trend, Psychology in Social Context: Issues and Debates provides an accessible introduction to current thinking and key ideas relating to the field of critical psychology. Taking a distinctive approach to addressing issues in psychology, this thought-provoking text considers a variety of historical controversies in psychology and the ways in which the discipline is embedded within particular socio-historical contexts. The team of authors draws on historical analysis to reveal the ways in which psychology interrelates with social context. Concepts are richly illustrated with many examples of how the discipline has engaged with such controversial social issues as race and IQ, psychology and gender, ethical issues in psychology, parapsychology, and the nature-nurture debate. Provocative and intellectually stimulating, Psychology in Social Context provides deep insights into the diverse nature of a discipline and its pursuit of the understanding of the mind and behaviour'--
Includes bibliographical references ( p. [257] -272) and index.
Keywords: Psychology -- Social aspects; Psychology -- History; Psychology